(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The paper examines the uprooted experiences and the struggle for survival of the migrants with particular reference to Imbolo Mbue’s Behold the Dreamers. Filled with hope for a better life people migrate from their native country to another. While doing so problems await the migrants in their migrated land where they become victims of identity crisis, racial discrimination, alienation, nostalgia and other cultural disorientation. Behold the Dreamers deals with the brutality of immigration system that prevails in America, and hence the paperattempts to bring out the toils and pains experienced by the diasporic communities in America, by the way of denying their opportunities, discrimination and alienation. It also throws light on the sufferings encountered by the immigrants, and the dysfunctional immigration system by which the immigrants find it difficult to survive in their migrated land. Independence is not at all possible in America for the immigrants, and this is being expressed through the life of Jende, the protagonist and Neni, his wife. The alienated feeling of the migrants and the struggle for existence of the immigrants are discussed in Diasporic perspective.